Development and evaluation of inactivated vaccines incorporating a novel Senecavirus A strain-based Immunogen and various adjuvants in mice - Wang, Bingliang; Gao, Fei; Hu, Ruijie; Huyan, Hanrong; Wang, Gaili; Cao, Zezhao; Zhao, Yue; Lu, Huijun; Song, Deguang; Gao, Feng; He, Wenqi; Lan, Yungang (Frontiers in Veterinary Science, 2024)
Porcine idiopathic vesicular disease (PIVD), one of several clinically indistinguishable vesicular diseases of pigs, is caused by the emerging pathogen Senecavirus A (SVA).Despite the widespread prevalence of porcine SVA infection, no effective commercial vaccines for PIVD prevention and control are available, due to high costs associated with vaccine testing in pigs, considerable SVA diversity, and SVA rapid evolution. In this study, SVA CH/JL/2022 (OP562896), a novel mutant SVA strain derived from an isolate obtained from a pig farm in Jilin Province, China, was inactivated then combined with four adjuvants, MONTANIDETM GEL02 PR (GEL 02), MONTANIDETM ISA 201 VG (ISA 201), MONTANIDETM IMG 1313 VG N (IMS1313), or Rehydragel LV (LV). The resulting inactivated SVA CH/JL/2022 vaccines were assessed for efficacy in mice and found to induce robust in vivo lymphocyte proliferation responses and strong IgG1, IgG2a, and neutralizing antibody responses with IgG2a/IgG1 ratios of <1. Furthermore, all vaccinated groups exhibited significantly higher levels of serum cytokines IL-2, IL-4, IL-6, and IFN as compared to unvaccinated mice. These results indicate that all vaccines elicited both Th1 and Th2 responses, with Th2 responses predominating. Moreover, vaccinated mice exhibited enhanced resistance to SVA infection, as evidenced by reduced viral RNA levels and SVA infection-induced histopathological changes. Collectively, our results demonstrate that the SVA-GEL vaccine induced more robust immunological responses in mice than did the other three vaccines, thus highlighting the potential of SVA-GEL to serve an effective tool for preventing and controlling SVA infection.